Functional assessment of military aircrew applicants in a hypobaric chamber. (1st July 2022) - Ang, T; Tan, D; Goh, B; Ng, W T; Tan, B B C; See, B
Abstract: Background: Aircrew are exposed to environmental pressure changes. In the Republic of Singapore Air Force (RSAF), applicants assessed to be at intermediate risk of otic barotrauma undergo a hypobaric chamber assessment ["trial of chamber" (TOC)] to functionally evaluate their suitability for military aircrew vocations. Aims: To identify factors associated with TOC failure among applicants with otorhinolaryngological conditions. Methods: All applicants to RSAF aircrew vocations who were assessed to be at intermediate risk of otic barotrauma over a 3-yr period were identified using the RSAF Aeromedical Centre's electronic database. Their medical records, as well as the TOC assessment records of the subset of applicants who underwent TOC, were reviewed for demographic data, clinical findings, and TOC outcomes. Results: Of the 483 identified applicants, 374 (77%) had abnormal otoscopic findings, 103 (21%) had rhinitis symptoms, and 6 (1%) had previous ENT surgery. 123 (25%) underwent TOC, of which 20 (16%) failed. Holding other predictor variables constant, the odds of TOC failure increased by 0.79 per unit decrease in BMI (95% CI 0.63–0.99), and the odds of TOC failure increased by 0.93 per kg decrease in body weight (95% CI 0.87–1.00). An abnormal tympanogram was not a statistically significant predictor of TOC failure (OR 1.96, 95% CI 0.59–6.42). Of the 47 applicants who passed TOC and were eventually recruited, none subsequently developed otic barotrauma (mean follow-up, 3.3 yr ± 1.5 yr). Conclusions: Applicants with lower weight and BMI are more likely to develop otic barotrauma with environmental pressure change. Tympanometry cannot be reliably used to identify applicants who would more likely pass TOC.